DIVINE ACTION, PROVIDENCE, AND THE THREE MAIN ARTICLES OF THE CREED - Durand, Emmanuel (Science et Esprit, 2021)
How to present God’s commitment in the world and in history in the most appropriate way? This article advances two proposals. First, to privilege the motif of God’s action as being the most integral such motif, compared to causality, event, and meaning. Second, to spell out Christian faith in Providence according to the three main articles of the Creed. The challenge of conceiving God’s sovereignty in an opaque world and in a shattered history remains, but the confession of faith nonetheless proves the best starting point and guideline.